1997
DOI: 10.1056/nejm199701093360203
|View full text |Cite
|
Sign up to set email alerts
|

Medical Care Costs and Quality of Life after Randomization to Coronary Angioplasty or Coronary Bypass Surgery

Abstract: In patients with multivessel coronary disease, coronary-artery bypass surgery is associated with a better quality of life for three years than coronary angioplasty, after the initial morbidity caused by the procedure. Coronary angioplasty has a lower five-year cost than bypass surgery only in patients with two-vessel coronary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
163
0
8

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 300 publications
(181 citation statements)
references
References 37 publications
10
163
0
8
Order By: Relevance
“…The C/E studies of revascularization for patients with stable angina included one based solely on modeling from secondary data (77) and one based directly on a clinical trial (29). Using decision analysis with a Markov model, Wong et al assessed the incremental cost effectiveness of angioplasty (PTCA) compared with medical therapy and CABG in different patients (77).…”
Section: Coronary Heart Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…The C/E studies of revascularization for patients with stable angina included one based solely on modeling from secondary data (77) and one based directly on a clinical trial (29). Using decision analysis with a Markov model, Wong et al assessed the incremental cost effectiveness of angioplasty (PTCA) compared with medical therapy and CABG in different patients (77).…”
Section: Coronary Heart Diseasementioning
confidence: 99%
“…The Bypass Angioplasty Revascularization Investigation followed the Wong analysis in 1997, and its results were quite different (29). This Investigation was a randomized experiment comparing PTCA and CABG, on an intentionto-treat basis, in patients with disease of one or two coronary vessels.…”
Section: Coronary Heart Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…In the late 1990 s, Hlatky et al showed that long-term cognitive function was similar after CABG surgery and coronary angioplasty in the majority of patients. 19 The International Study of Postoperative Cognitive Dysfunction (ISPOCD) group 20 showed that POCD was present in 10.4% of elderly patients one to two years after non-cardiac surgery. This rate of cognitive decline was almost identical (10.6%) to the age-adjusted non-surgical controls tested at the same time interval.…”
Section: Discussionmentioning
confidence: 99%